Digital Media, Activism, and Social Movements' Outcomes in the Policy Arena. The Case of Two Anti-Corruption Mobilizations in Brazil - Alice Mattoni (Coordinamento SIBA, 2021)
This article investigates the role of digital media in mechanisms that sustain the achievement of social movement outcomes during key phases of mobilizations that aim to impact policymaking. It does so by comparing two anti-corruption initiatives in Brazil that became legislative bills through popular petition and included the employment of digital media to support them: the Ficha Limpa (or Clean State Law) and the Ten Measures Against Corruption (TMAC) campaigns. Based on in-depth interviews with key activists and secondary sources, including an analysis of the campaigns' digital media content, this study evaluates three types of outcomes in the political realm: access, agenda, and policy responsiveness. Although both anti-corruption initiatives elicited public preference and placed their legal inputs in the public agenda of the political system, they were not equally successful in converting their ideas into new legislation. The Ten Measures was a campaign that occurred when the digital affordances for civil society actors were considerably higher, but it did not achieve positive outcomes as the Ficha Limpa did. This article suggests that initiatives focusing more on online mobilization strategies without a clear advocacy approach to negotiate with (and pressure) public officials do not seem to be enough to promote policy changes.